Women’S Empowerment: a Conceptual Analysis: Exploring the Intersection of Gender Inequality and Occupational Segregation (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Women’s Empowerment educates and empowers women, who are homeless, withthe skills and confidence necessary to secure a job, create a healthylifestyle, and regain a home for themselves and their children. The entry of women into a specific trade signaled a downgrading of thetrade. With industrialization, women still earned one-third to one-half ofmen's wages. New occupations were added for women over time, but these for themost part were ones previously filled by males, but downgraded in status andpay for women. These jobs included secretaries and typists in businesses, storeclerks in the new department stores, and teaching. Increased demarcation in theindustrial economy was the strict delineation between men's and women's work.